2022
DOI: 10.1186/s12879-022-07271-z
|View full text |Cite
|
Sign up to set email alerts
|

Time to complete hepatitis C cascade of care among patients identified during mass screening campaigns in rural Rwanda: a retrospective cohort study

Abstract: Background Since the discovery of direct-acting antivirals, treatment for hepatitis C virus (HCV) is increasingly accessible in low-resource settings, but quality of care in these settings is not known. We described progression through the cascade of care among individuals who screened positive for HCV antibodies during a mass screening campaign in Kirehe and Kayonza, two rural Rwandan districts, in September 2019. Methods This retrospective cohort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
(31 reference statements)
0
4
0
Order By: Relevance
“…In addition, HNSC patients may have even started treatment due to the lack of clinical conditions, such as neoplasms or serious comorbidities. Not having genotyping or HCV-PCR test within a year are also bureaucratic reasons that interfere with the delay in starting HCV therapy, which is unfortunate given the possibility of simplified protocols with pangenotypic regimens[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, HNSC patients may have even started treatment due to the lack of clinical conditions, such as neoplasms or serious comorbidities. Not having genotyping or HCV-PCR test within a year are also bureaucratic reasons that interfere with the delay in starting HCV therapy, which is unfortunate given the possibility of simplified protocols with pangenotypic regimens[ 15 , 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2018, 71.1 million people were estimated as worldwide chronic carriers of HCV; approximately 18 millions of them were in Africa (13) and are at risk of HCC development (14). HCV prevalence in SSA and North Africa is estimated at 2.1-3.3% and 2.3-7.7%, respectively (15).…”
Section: Hcvmentioning
confidence: 99%
“…Given the magnitude of Egypt's HCV and HCC problems, the extensive HCV treatment program could significantly impact the country's HCC figures shortly (19). Similarly, the Rwandan viral hepatitis program began in 2011, and the national hepatitis elimination strategy declared an ambitious goal of treating 90% of people affected by 2024 (13).…”
Section: Hcvmentioning
confidence: 99%
“…One study that assessed the cascade of care in two rural districts of Rwanda found that 83.4% of patients tested for HCV had detectable viral loads. Almost everyone considered for treatment initiated treatment, while 93.7% of patients achieved SVR12 [ 25 ]. Although this study provided information on patients’ journeys in HCV care, the findings cannot be generalized, since the study was conducted in only two of the poorest districts of Rwanda and used a small sample size.…”
Section: Introductionmentioning
confidence: 99%